Mouse Model of Neurological Complications Resulting from Encephalitic Alphavirus Infection - Ronca, Shannon E.; Smith, Jeanon; Koma, Takaaki; Miller, Magda M.; Yun, Nadezhda; Dineley, Kelly T.; Paessler, Slobodan (Frontiers in Microbiology, 2017)
Long-term neurological complications, termed sequelae, can result from viral encephalitis, which are not well understood. In human survivors, alphavirus encephalitis can cause severe neurobehavioral changes, in the most extreme cases, a schizophrenic-like syndrome. In the present study, we aimed to adapt an animal model of alphavirus infection survival to study the development of these long-term neurological complications. Upon low-dose infection of wild-type C57B/6 mice, asymptomatic and symptomatic groups were established and compared to mock-infected mice to measure general health and baseline neurological function, including the acoustic startle response and prepulse inhibition paradigm. Prepulse inhibition is a robust operational measure of sensorimotor gating, a fundamental form of information processing. Deficits in prepulse inhibition manifest as the inability to filter out extraneous sensory stimuli. Sensory gating is disrupted in schizophrenia and other mental disorders, as well as neurodegenerative diseases. Symptomatic mice developed deficits in prepulse inhibition that lasted through 6 months post infection; these deficits were absent in asymptomatic or mock-infected groups. Accompanying prepulse inhibition deficits, symptomatic animals exhibited thalamus damage as visualized with H&E staining, as well as increased GFAP expression in the posterior complex of the thalamus and dentate gyrus of the hippocampus. These histological changes and increased GFAP expression were absent in the asymptomatic and mock-infected animals, indicating that glial scarring could have contributed to the prepulse inhibition phenotype observed in the symptomatic animals. This model provides a tool to test mechanisms of and treatments for the neurological sequelae of viral encephalitis and begins to delineate potential explanations for the development of such sequelae post infection.